2018
DOI: 10.1073/pnas.1802470115
|View full text |Cite
|
Sign up to set email alerts
|

Sinking particles promote vertical connectivity in the ocean microbiome

Abstract: SignificanceProkaryotes dominate the living biomass and the biological diversity of the ocean, one of the largest ecosystems on earth. The sinking of particles is a widespread mechanism that transports materials to the deep ocean, with a significant role in the global carbon cycle. Whether this process constitutes a global dispersal pathway for prokaryotic diversity connecting surface communities to those in the dark ocean has never been tested. Here we show that surface and deep-sea prokaryotic communities ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

28
252
5
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 187 publications
(305 citation statements)
references
References 75 publications
28
252
5
5
Order By: Relevance
“…Indeed, we observed that OTUs originally categorized as bimodal or logistic based on their presence in surface free‐living communities, largely increased their relative abundances at other depth layers and size‐fractions (Supporting Information Figure ). This indicates that globally rare surface taxa may become abundant in these other habitats, in agreement with the recently reported strong connectivity between surface and deep microbial communities via sinking particles or water masses movement (Luna et al, ; Mestre et al, ; Wilkins et al, ). Exploring taxa distributions across different environments may thus help determine how differently environmental transitions or boundaries affect the distribution of each taxon.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Indeed, we observed that OTUs originally categorized as bimodal or logistic based on their presence in surface free‐living communities, largely increased their relative abundances at other depth layers and size‐fractions (Supporting Information Figure ). This indicates that globally rare surface taxa may become abundant in these other habitats, in agreement with the recently reported strong connectivity between surface and deep microbial communities via sinking particles or water masses movement (Luna et al, ; Mestre et al, ; Wilkins et al, ). Exploring taxa distributions across different environments may thus help determine how differently environmental transitions or boundaries affect the distribution of each taxon.…”
Section: Discussionsupporting
confidence: 88%
“…This, coupled to the fact that our perception of taxa occurrence is largely dependent on the sequencing resolution (Gibbons et al, ; Ruiz‐González et al, ), explains why our understanding of the ecology and mechanisms associated with microbial cosmopolitanism, dominance or rarity is far behind that of macroorganisms. In this context, the identification of bacterial spatial “behaviours” across large spatial scales is emerging as a promising way to gain insight into microbial biogeography drivers (Mestre et al, ; Niño‐García et al, ; Ruiz‐González et al, , ). For example, the SpAD approach allowed discovering that hydrologic transport from rivers explained the presence of most rare bacteria in boreal lakes, but at the same time inoculated taxa able to thrive in lake conditions (Niño‐García et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, some microbial taxa may overcome dispersal limitation imposed by hydrographic or other physical barriers (Spencer‐Cervato and Thierstein, ; Galand et al, ). Oceanic dispersal of diverse plankton has been shown (Sexton and Norris, ; Malviya et al, ; Whittaker and Rynearson, ); however, such large vertical range – from surface waters to the bathypelagic realm – for the same taxon is not well‐documented, but has been observed among taxa associated with large sinking particles (Mestre et al, ). A second important point is that deep sea microbes may hydrolyze components of HMW‐OM at rates comparable to those observed in much shallower waters (Figs and ).…”
Section: Discussionmentioning
confidence: 99%